THE EFFECT OF FEEDING TANNIN-PROTECTED FISH MEAL ON THE INCREASE OF BODY WEIGHT AND BODY SIZE OF LOCAL SHEEP - Rohimat, agung (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2025)
Protein protection using tannins is expected to increase utilization efficiency protein in ruminants. .This research aims to determine the effect of adding tannin-protected fish meal to the ration on the growth of body weight and body size of local sheep. The method used was an experiment with a Completely Randomized Design (CRD) followed by the Duncan test. There were four ration treatments and five replications. P0 = Basal feed (80% field grass + 20% tofu dregs), P1 = Basal feed + 4% fish meal, P2 = Basal feed + 2% tannin-protected fish meal, P3 = Basal feed + 4% tannin-protected fish meal. The result of statistical analysis concluded that adding tannin-protected fish meal for a period of 42 days had no significant effect on increasing body weight and body size of local sheep. Keywords : sheep, fish meal, tannin, body weight, body size